2023
DOI: 10.1021/acsaenm.2c00270
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Compatibilization of Impact Copolymer Polypropylene and Organically Modified Mesoporous Silica to Prepare Composites Possessing Enhanced Mechanical Properties

Abstract: Mesoporous silica was evaluated as functionalized filler in impact copolymer polypropylene (ICP) in its original form as well as after organic modification. Mesoporous silica was synthesized by base-catalyzed hydrolysis of tetraethyl orthosilicate in the water–acetone medium. The organic modification of mesoporous silica was carried out using commercially available silane with a terminal unsaturated bond and by synthesizing silane precursor by chemical treatment via TEMPO-initiated thiol–ene chemistry to intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In the first step of the post-modification procedure, 3-(trimethoxysilyl) propyl methacrylate was treated with mono-thioglycerol via thiol-ene chemistry using TEMPO as an initiator. [24][25][26][27][28] The reaction mixture was continuously stirred until the disappearance of NMR signals corresponding to vinyl protons. The synthesis of modified silane was confirmed using 1 H NMR, as shown in Figure 1.…”
Section: Characterization Of Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step of the post-modification procedure, 3-(trimethoxysilyl) propyl methacrylate was treated with mono-thioglycerol via thiol-ene chemistry using TEMPO as an initiator. [24][25][26][27][28] The reaction mixture was continuously stirred until the disappearance of NMR signals corresponding to vinyl protons. The synthesis of modified silane was confirmed using 1 H NMR, as shown in Figure 1.…”
Section: Characterization Of Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…The extensively high surface area of mesoporous substrates allows effective surface modification to alter the bulk properties as desired. [22][23][24] Though silica nanoparticles have been extensively explored as additives to improve various properties of PP films, mesoporous silica hasn't been studied for PP film formulations. In this paper, we have synthesized mesoporous silica particles and analyzed its performance as an additive on thermal, mechanical, and optical properties of tubular quenched polypropylene (TQPP) films as compared to the commercial silica grade used commonly in industries for preparing TQPP films.…”
Section: Introductionmentioning
confidence: 99%
“…They show promise in areas as diverse as heterogeneous catalysis, , energy storage, adsorption and separations, and biomedical devices. These siliceous materials are synthesized in a wide range of morphologies and by several processes to meet the diverse physical and chemical requirements of these applications. Common materials include composites, ,, aerogels and xerogels, ,,, films and membranes, , particles, and microstructured monoliths. , Preparation methods include sol–gel processing, ,, templating methods, ,,,,, deposition, and a variety of other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These spectra gave information on the environment around the silicon as well as its organic functionalization. In 29 Si spectra, the signals due to the presence of a single silanol group (Q3) [(≡SiO) 3 SiOH] and siloxane moiety Q4 [(≡SiO) 4 Si] were found in the range −100 to −115 ppm. T2 [(SiO) 2 Si(OH)R] and T3 [(SiO) 3 SiR] in MSN-SH and MSN-SO 3 H spectra indicate the presence of a covalently attached organic moiety (propyl thiol and propyl sulfonic acid) to silica.…”
mentioning
confidence: 99%
“…In addition, mesoporous silica nanoparticles functionalized with sulfonic acids have been utilized in a wide range of catalytic reactions . These reactions include the making of biodiesel, acetalization reactions, condensations, and the preparation of biologically active compounds. ,,, Aboelhassan et al synthesized a variety of sulfonic acid functionalized silica nanoparticles for the esterification of linoleic acid . They found that these catalysts had exceptional performance in the esterification of linoleic acid, with a 100% conversion rate in a reaction time of about 2 h. Rhijn et al synthesized functionalized mesoporous silica nanoparticles for catalyzing the synthesis of bisfurylalkanes and polyol esters. , They observed that sulfonic acid functionalized mesoporous silica nanoparticles have the potential for catalyzing reactions in which zeolites fail.…”
mentioning
confidence: 99%